(untitled) - Ho Hue-Tam Tai (Cambridge, Massachusetts, 1992)
The book is about the role of radicalism in the early phase of the Vietnamese Revolution and its eventual displacement by Marxism-Leninism as the dominant force in reshaping anticolonial politics and as the source of language for discussing cultural, social, and political issues. The events of the 1920s and 1930s were crucial in the evolution of modern VietNam. In focusing on the strikes of the mid-1920s, this book shows the political and intellectual options of the beginning, experimental, and most individualistic stage of the Vietnamese Revolution. In the early years of the Revolution radicalism was the domonant force in anticolonial politics. The displacement of radicalism by communism has obscured its role as a nonideological reaction to both colonial rule and native accommodation to that rule. The book shows that radicalism arose from the combined national and personal concerns of young Vietnamese, who saw a symmetry between the national struggle for independence from colonial rule and their own efforts to emancipate themselves from the oppressiveness of native social institutions and the deadweight of tradition
Keywords: radicalism - vietnam - history,vietnam - politics and government - 1858-1945